Mujeres y filosofía: la decisión de Hiparquia - Sáenz Benavides, Laurencia (2015)
This article proposes to analyze the arguments developed by three seventeenth Century philosophers on the equality between men and women. It aims to show the relevancy of a tradition that criticized sexist topics in the philosophical discourse for the account of a history of philosophy from a non-androcentric perspective.